ORGANIZATIONAL AND METHODICAL PROBLEMS OF CONSTRUCTING THE EDUCATIONAL PROCESS OF MILITARY FACULTY STUDENTS’ PHYSICAL TRAINING - Орленко, Н. А. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The article deals with the problems of physical training of the military faculty students at higher educational institutions. Physical training has been determined to be an integral part of the overall system of training and education of personnel of the Ukrainian Armed Forces, whose purpose is to ensure the servicemen’ physical readiness for professional activity. The essence of the physical training optimization process proves to involve: changing the organization of the educational process by introducing the technological component